O erro corrigível e a ilusão inevitável na Crítica da Razão Pura de Kant - Dutra, Elias Sergio (Universidade Federal de São Carlos, 2008)
The purpose of this work is to examine the problem of error and transcendental illusion in Kant s Critique of Pure Reason as two correlate, but sharply distinct aspects of his critique on dogmatic metaphysics. Following Kant s indications, we analyze his paradoxical doctrine that error is avoidable even if its positive source, transcendental illusion, is considered natural and inherent to human reason. Accordingly, we first analyze the status of error as a property of judgments in general Kant s thesis is that error can be explained in terms of a double influence that, if unnoticed, deviates the judgment from truth: imagination and sensibility. Under each of these influences, the human understanding helds merely subjective for objective principles of knowledge, thereby attaining error instead of true cognition. Secondly, applying this general analysis of error to one specific case, we focus our analyze on the issue of transcendental illusion involved in the transcendental idea of God In this particular case, we try to show how the legitimate demand of reason for a complete explanation (underlying the concept of God as an ens realissimum) allows room for a dialectic illusion, which holds that this concept of reason for a necessarily real and existing being. Finally, we try to point out the positive contribution to metaphysics which arises from Kant s distinction between judgmental error and transcendental illusion.
Keywords: Conhecimento; Metafísica; Erro; Ilusão; Númeno; Deus; Knowledge; Metaphysics; Noumenon; God; Error; Illusion; CIENCIAS HUMANAS::FILOSOFIA